Correction: In situ encapsulation of core–shell-structured Co@Co3O4 into nitrogen-doped carbon polyhedra as a bifunctional catalyst for rechargeable Zn–air batteries. Issue 36 (8th September 2020) - Guo, Ziyang; Wang, Fengmei; Xia, Yuan; Li, Jinli; Tamirat, Andebet Gedamu; Liu, Yanru; Wang, Lei; Wang, Yonggang; Xia, Yongyao
Abstract : Correction for ' In situ encapsulation of core–shell-structured Co@Co3 O4 into nitrogen-doped carbon polyhedra as a bifunctional catalyst for rechargeable Zn–air batteries' by Ziyang Guo et al., J. Mater. Chem. A, 2018, 6, 1443–1453, DOI: ; 10.1039/C7TA09958D .